Pengaruh Model PBL Berbantuan Media PowerPoint Interaktif Terhadap Kemampuan Berhitung Matematika Kelas II SD - Kusumadewi, Rida Fironika; Aini, Dwi Qurrotu' (Didaktika, 2025)
The mathematics lesson on addition and subtraction word problems for second-grade students in elementary school can enhance students' problem-solving skills and enable them to analyze information to find solutions. According to students, mathematics is considered a boring and difficult subject, especially in the material of addition and subtraction word problems, where students often struggle to understand the sentences, making it hard for them to solve the problems. Therefore, the objective of this research is to test and determine the effect of the Problem-Based Learning (PBL) model assisted by interactive PowerPoint learning media on the mathematical calculation abilities of second-grade students at the Primary School of Islam Sultan Agung 4. This study uses a quantitative research method with a pre-experimental type, specifically the one-group pretest-posttest design, and employs a test as the data collection technique. The sample consists of 20 students. Based on the normality test results, the pretest has a sig. value of 0.627 ˃ α, indicating that the data is normally distributed, while the posttest has a sig. value of 0.768 ˃ α, also indicating normal distribution. In the hypothesis test using the paired-sample t-test, the sig. (2-tailed) value is 0.000 ˂ 0.05, suggesting a significant difference in mathematical calculation abilities before and after the treatment using the PBL model assisted by interactive PowerPoint media. After the treatment, students became more active in learning, able to engage in discussions, divide tasks within groups, and differentiate sentences that indicate addition and subtraction operations in word problems, ultimately improving their calculation abilities.